Answer:
2ab(a + 3b)
Step-by-step explanation:
2a²b + 6ab²
Factor out 2ab
2ab(a + 3b)
That means the average of all data point equal:
(99+122+103+113+109+x)/6 = 103
===> (546+x)/6 = 103===> 546+x=618 & x=618-546=72, so x =72
Divide 6 by
![\frac{3}{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B4%7D%20)
![\frac{6}{1}](https://tex.z-dn.net/?f=%20%5Cfrac%7B6%7D%7B1%7D%20)
÷
![\frac{3}{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B4%7D%20)
Change
![\frac{3}{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B4%7D%20)
to a reciprocal
![\frac{6}{1}](https://tex.z-dn.net/?f=%20%5Cfrac%7B6%7D%7B1%7D%20)
×
![\frac{4}{3}](https://tex.z-dn.net/?f=%20%5Cfrac%7B4%7D%7B3%7D%20)
=
Simplify and your answer is 8
-18.2 + 3.6= -14.6 is the answer to the question
Answer:
4x +y = 3
Step-by-step explanation:
Perpendicular lines have slopes that are the negative reciprocals of one another. When the equation of the line is written in standard form like this, the equation of the perpendicular line can be written by swapping the x- and y-coefficients and negating one of them. Doing this much would give you ...
4x +y = (constant)
Note that we have chosen to make the equation read 4x+y, not -4x-y. The reason is that "standard form" requires the leading coefficient to be positive.
Now, you just need to make sure the constant is appropriate for the point you want the line to go through. So, it needs to be ...
4(2) +(-5) = constant = 3
The line of interest has equation ...
4x + y = 3